PWE-264 Laparoscopic versus open T4 colonic cancer resection. (22nd June 2015) - King, A; Dixon, J; Harji, D; Sagar, P
Abstract : Introduction: The role of laparoscopic resection in T4 colon cancer is controversial, with the early laparoscopic randomised trials reporting variable outcomes in this cohort of patients. We aim to examine the clinical and oncological outcomes between laparoscopic and open T4 colon cancer resections. Method: All consecutive patients undergoing surgery for a radiological presumed T4 colon cancer between 2009 and 2012 from a prospectively maintained database were identified. Data were collected on patient demographics, operative detail, histological data and follow up status. Results: 221 patients were identified, with 106 (48.0%) undergoing open surgery and 115 (52.0%) undergoing laparoscopic surgery. Conversation rate was 12.1%. The two groups were similar in pre-operative staging. R0 resection rate was achieved in 75.9% with similar rates in the laparoscopic and open group, 40.8% and 35.1% respectively, p = 0.74. Complication rates were similar between the two groups (laparoscopic 19% versus open 23.5%, p = 0.06). Median length of stay was shorter in the laparoscopic group compared to the open group (9 vs. 14 days, p = 0.05). Overall 3-year survival was similar in both groups, (laparoscopic 39% versus open 25%, p = 0.27). Conclusion: Laparoscopic surgery is feasible in T4 colon cancers with comparable clinical and oncological outcomes, with the advantage of faster recovery. Disclosure of interest: None Declared.